2015
DOI: 10.1016/j.it.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Boosting vaccine efficacy the natural (killer) way

Abstract: Coordination of the innate and adaptive immune systems is paramount to the development of protective humoral and cellular immunity following vaccination. Natural killer (NK) cells are front-line soldiers of the innate immune system, and recent studies have revealed functions for NK cells in long-lived immune memory and the regulation of adaptive immune responses. These findings suggest that NK cells may play important roles in the development of efficacious vaccines, as well as, in some contexts, failed immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 153 publications
0
62
0
Order By: Relevance
“…The immunologic environment at the time of CD4 + T‐cell priming thus has an important impact on initial Tfh induction, and regulatory cell populations including FoxP3 +  CD4 + regulatory T cells (Tregs),215, 216 IL‐10‐producing regulatory B cells,217, 218 and natural killer (NK) cells219 may all modulate the generation of Tfh cells and hence influence GC formation and the subsequent humoral response.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…The immunologic environment at the time of CD4 + T‐cell priming thus has an important impact on initial Tfh induction, and regulatory cell populations including FoxP3 +  CD4 + regulatory T cells (Tregs),215, 216 IL‐10‐producing regulatory B cells,217, 218 and natural killer (NK) cells219 may all modulate the generation of Tfh cells and hence influence GC formation and the subsequent humoral response.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Despite this, recent evidence in mice, humans and non-human primates confirms that NK cells can be long-lived and are capable of exerting antigen-specific immune responses against haptens and viruses (911). While NK cells have long been characterized as bridging the innate and adaptive immune systems, recent findings suggest that NK cells may develop antigen specific responses that can be manipulated through vaccination (9,12). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to suppressing T cell expansion and cytokine production, some models have shown that suppressive NK cells/ILCs produce IL-10 (refs. 35,36), inhibit B cell function and memory 37,38 , and dampen immune responses by modulating DC function 3941 , as well as limiting immunity by killing CD8 + T cells 19, 20 . While the majority of studies have described immunosuppressive ILCs as NK cells, the various shared and distinct properties of suppressive ILCs when compared to conventional NK cells and other ILC subsets are not well defined.…”
mentioning
confidence: 99%